UNVEILING THE POWER OF K-MEANS IMAGE SEGMENTATION ALGORITHM: A COMPREHENSIVE REVIEW - Sattarov , M.A; Xaniyev , N; Mardanov , A.K (Educational Research in Universal Sciences, 2023)
Image segmentation is a crucial step in computer vision and image processing, serving as the foundation for various applications such as object recognition, medical imaging, and autonomous vehicles. Among the plethora of image segmentation techniques, the K-Means algorithm has gained significant attention for its simplicity, efficiency, and versatility. This article provides a comprehensive review of the K-Means Image Segmentation Algorithm, delving into its principles, applications, strengths, weaknesses, and recent advancements.